Microplásticos em águas subterrâneas de área urbana - Matos, Felipe Lúcio Duda (2021)
Microplastics have been more studied in marine environments, because the oceans are the environmental compartment that concentrates the greatest amount of plastic microparticles. In freshwater environments, studies are less frequent, concentrating research on the detection of microplastics, in living organisms and in public health. In groundwater, the microplastics theme are even more scarce. These facts motivated the study to evaluate the presence of microplastics in groundwater in the urban perimeter of the municipality of Cuiabá-MT. 508 underground water wells were built in the north, south, east and west of the urban area, serving domestic and industrial supply uses. For the detection of microplastic, 11 wells were monitored, with the collection of 500 L of water, and subsequent filtration through 0.063 mm mesh sieves. For laboratory quantification, the microplastics were separated and counted manually, using a stereoscope. From the results obtained, it can be concluded that 90% of the monitored wells meet the domestic supply, and in 82% of these, at least 1 plastic microparticle was found. The transparent fiber was the most common form and it was statistically found that there is no relationship between the amount of microplastics and the characteristic variables of the wells, such as flow rate, depth, drilling time and the region where the well is located. Several studies report the presence of microplastics in drinking water, requiring research to assess the implications of ingestion on public health, reinforcing the need to implement the monitoring of microparticles in water and establish control standards, through norms and legislation around the world.